THE ROLE OF ATTITUDE TOWARDS INTERNET OF THINGS (IOT) IN RELATION TO TECHNOLOGY ACCEPTANCE MODEL IN THAILAND - Narakorn, Prasittichai; Seesupan, Tummatinna (PEOPLE: International Journal of Social Sciences, 2019)
The objectives of this study is to investigate the Technology Acceptance Model (TAM) which derives from following factors: Perceived Ease of Use, Perceived Usefulness, Attitude towards Internet of Things, and Continuance intention to use who use products from Internet of Things in Thailand. The researchers applied the quantitative method to 272 users who bought products from Internet of Things and analyzed in term of frequency, mean and Structural Equation Model (SEM) analysis by AMOS. The research findings indicated that Perceived Ease of Use, Perceived Usefulness, Attitude towards Internet of Things had significantly positive influence to Continuance intention to use (p < .05).